Identification of the natural breeding sites of sandflies (Diptera: Psychodidae: Phlebotominae), potential vectors of leishmaniasis, in the province of Chaco, Argentina - Parras, Matías Ariel (2012)
The aim of this work was to identify the natural breeding sites of sandflies in the province of Chaco, Argentina, for the first time. Preliminary studies were conducted in two different phytogeographic regions: dry Chaco (Parque Provincial Pampa del Indio), in January 2010, and humid Chaco (Resistencia, Margarita Belén and Colonia Benítez), from May-September 2010. A total of 127 samples were collected (Pampa del Indio: 15, Resistencia: 37, Margarita Belén: 36, Colonia Benítez: 39). A female of Migonemyia migonei was found in Pampa del Indio at the base of a bromeliad in the summer (January) and a pupal exuvium of a phlebotomine fly was found in Resistencia, in a place where dogs rested, in the winter (July). These findings highlighted these two sites as potential breeding sites. Because the existence of potential natural breeding sites for sandflies has been demonstrated in both forest and periurban areas, expanding the search efforts and characterising these sites will enable the development of specific study designs to gain insight into the spatial distribution of the risks posed by these vectors. The resulting information will serve as a basis for proposing and evaluating vector control measures.